Turning over a New Leaf Change and Development in the Medieval Book - McKitterick, Rosamond; Lieftinck, G. I., 1902-1994; Thomson, Rodney M.; McKitterick, Rosamond; Kwakkel, Erik, 1970-; Project Muse. (2012)
"Books before print -manuscripts- were modified continuously throughout the medieval period. Focusing on the ninth and twelfth centuries, this volume explores such material changes as well as the varying circumstances under which handwritten books were produced, used and collected. An important theme is the relationship between the physical book and its users. Can we reflect on reading practices through an examination of the layout of a text? To what extent can we use the contents of libraries to understand the culture of the book? The volume explores such issues by focusing on a broad palette of texts and through a detailed analysis of manuscripts from all corners of Europe"--Publisher's description.
Introduction: Gerard Isaac Lieftinck / J.P. Gumbert -- Glossaries and other innovations in Carolingian book production / Rosamond McKitterick -- Biting, kissing and the treatment of feet : the transitional script of the long twelfth century / Erik Kwakkel -- The place of Germany in the twelfth-century Renaissance : books, scriptoria and libraries / Rodney Thomson.
Expanded versions of three lectures given as the inaugural Lieftinck lectures in honor of G.I. Lieftinck at the Leiden University Library in 2010-2011.
Includes bibliographical references (pages 145-163) and indexes.
Description based on print version record.
Keywords: Civilization, Medieval -- 12th century; Manuscripts, Medieval; Books -- History -- 400-1450.; Electronic books